Up-conversion Photoluminescence in a Fluorophosphate Glass Matrix Doped with Yb/Er – Effects of Doping Levels - Jarocka, Agata; Płochocki, Karol; Fetliński, Bartosz; Jurczenia, Karol; Pietrzak, Tomasz K.; Wasiucionek, Marek (Photonics Letters of Poland, 2026)
In this work, two series of glasses of the NaF–Al2O3–P2O5 ternary system with the Na3Al2(PO4)2F3 nominal composition, doped with Er3+ (1% and 0.5%) and Yb3+ ions were synthesized by a standard melt-quenching method and their up-conversion photoluminescence properties were studied. The as-received amorphous materials were excited by the IR laser radiation with a wavelength of 976 nm, and their emission spectra in the visible range were measured. The optical measurements were focused on the up-conversion photoluminescence spectra in the visible range. It was found that stronger up-conversion effects were observed for the series containing 1 wt% Er2O3. In the case of 0.5 wt% Er2O3, the emission response was weaker, comparable with the background noise. Full Text: PDF References F. Auzel, "Upconversion and Anti-Stokes Processes with f and d Ions in Solids", Chem. Rev. 104, 139 (2004) CrossRef A. Edgar,"Luminescent Materials", in: G. Blasse, B.C. Grabmaier (Eds.), Springer Handbooks, pp.983-996, Springer (2007) CrossRef J. Zhou, Q. Liu, W. Feng, Y. Sun, F. Li, "Upconversion Luminescent Materials: Advances and Applications", Chem. Rev. 115, 395 (2015). CrossRef F. Wang, X. Liu, "Recent advances in the chemistry of lanthanide-doped upconversion nanocrystals", Chem. Soc. Rev. 38, 976 (2009). CrossRef J. Huang, L. Yan, S. Liu, L. Tao, B. Zhou, "Expanding the toolbox of photon upconversion for emerging frontier applications", Mater. Horizons 9, 1167 (2022). CrossRef J.R. Lakowicz, Principles of Fluorescence Spectroscopy, 3rd ed., Springer Nature, Netherlands, 2006. CrossRef G.A. Kumar, D.-X. Liu, Y. Tian, M.G. Brik, D.K. Sardar, "5d–4f emission of Eu2+ and electron-vibrational interaction in several alkaline earth sulfides doped with Eu2+ and Er3+", Opt. Mater. (Amst). 50, 199 (2015). CrossRef G. Liu, "Advances in the theoretical understanding of photon upconversion in rare-earth activated nanophosphors", Chem. Soc. Rev. 44, 1635 (2015). CrossRef K.W. Krämer, D. Biner, G. Frei, H.U. Güdel, M.P. Hehlen, S.R. Lüthi, "Hexagonal Sodium Yttrium Fluoride Based Green and Blue Emitting Upconversion Phosphors", Chem. Mater. 16, 1244 (2004). CrossRef A. Nadort, J. Zhao, E.M. Goldys, "Lanthanide upconversion luminescence at the nanoscale: fundamentals and optical properties", Nanoscale 8, 1313 (2016). CrossRef T.K. Pietrzak, A. Gołębiewska, J. Płachta, M. Jarczewski, J. Ryl, M. Wasiucionek, J.E. Garbarczyk, "Photoluminescence of partially reduced Eu2+/Eu3+ active centers in a NaF–Al2O3–P2O5 glassy matrix with tunable smooth spectra", J. Lumin. 208, 322 (2019). CrossRef E. Kolobkova, N. Nikonorov, A. Babkina, A. Grabtchikov, I. Khodasevich, M. Korolkov, "Concentration dependence of upconversion luminescence of Er3+/Yb3+ in the fluorophosphate glasses with small phosphates content", Opt. Mater. (Amst). 109, 110279 (2020). CrossRef E. Kolobkova, A. Alkhlef, N. Kuzmenko, I.A. Khodasevich, A. Grabtchikov, "NIR and visible luminescence of Er3 +/Yb3+ co-doped fluorophosphate glasses with small additives of phosphates", J. Lumin. 235, 118033 (2021). CrossRef J.-M. Le Meins, O. Bohnke, G. Courbion, "Ionic conductivity of crystalline and amorphous Na3Al2(PO4)2F3", Solid State Ionics 111 (1998) 67-75. CrossRef A. Jarocka, B. Fetliński, P. Dębowski, T.K. Pietrzak, K. Jurak, M. Wasiucionek, "Facile and cost-effective technique to control europium oxidation states in glassy fluorophosphate matrices with tunable photoluminescence", Sci. Rep. 12, 1 (2022). CrossRef S. Kaniyarakkal, K. Culala Rajasekharaudayar, R. Dagupati, Y. Li, Z. Chen, V.S. Nair, S. Edappadikkunnummal, "Down conversion and efficient NIR to visible up-conversion emission analysis in Ho3+/Yb3+ co-doped tellurite glasses", Bol. La Soc. Esp. Ceram. y Vidr. 62, 379 (2023). CrossRef V.K. Tikhomirov, G. Adamo, A.E. Nikolaenko, V.D. Rodriguez, P. Gredin, M. Mortier, N.I. Zheludev, V. V Moshchalkov, "Cathodo- and photoluminescence in Yb3+-Er3+ co-doped PbF2 nanoparticles", Opt. Express 18, 8836 (2010). CrossRef